2013 36th International Conference on Telecommunications and Signal Processing (TSP) 2013
DOI: 10.1109/tsp.2013.6613943
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and measuring the co-existence between LTE and DVB-T2-Lite services

Abstract: The development and effective use of wireless communication systems to provide mobile services is rapidly increasing. Nowadays, the world´s most perspective standards to provide wireless multimedia services in high quality are LTE (Long-Term Evolution) and DVB-T2 Lite (DVB-2 nd Generation Terrestrial). On the other hand, these wireless multimedia systems can many times operate in a neighboring frequency spectrum. Therefore, as a result, numerous co-existence scenarios are possible. The focus of this paper is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In [7] and [8] it was concluded that an external filter, between the TV antenna and the DTT receiver is required when the DTT receiver is near to the LTE base station. In [9], [10] and [11], it was shown that the performance of the broadcast technology (DVB-T, DVB-T2 and T2-Lite) can be seriously affected by an adjacent LTE signal without any guard band in-between. LTE interference Protection Ratios (PR) for DVB-T (Digital Video Broadcast -Terrestrial) and DVB-T2 (Terrestrial 2 nd Generation) can be found in [12] and [13], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In [7] and [8] it was concluded that an external filter, between the TV antenna and the DTT receiver is required when the DTT receiver is near to the LTE base station. In [9], [10] and [11], it was shown that the performance of the broadcast technology (DVB-T, DVB-T2 and T2-Lite) can be seriously affected by an adjacent LTE signal without any guard band in-between. LTE interference Protection Ratios (PR) for DVB-T (Digital Video Broadcast -Terrestrial) and DVB-T2 (Terrestrial 2 nd Generation) can be found in [12] and [13], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We have provided a detailed description of LTE and DVB-T2-Lite coexistence in our previous works [30] and [31]. Based on data collected from the mentioned measurements, we made a dense description (linear model) of coexistence.…”
Section: Simulation Setupmentioning
confidence: 99%
“…For evaluating the interaction of the described coexistence scenarios between DVB-T2-Lite and LTE RF signals, the same measurement testbed was used as described in our previous works ( [30] and [31]). The whole measurement campaign was implemented on the seventh floor of the building of BUT, FEEC, DREL (see Figure 2).…”
Section: Measurement Setupmentioning
confidence: 99%
“…This co-primary operation between LTE-A and broadcasting receiver may cause destructive interference between the two services [7,8] and can affect on the system performance [9][10][11]. In the current coexistence literature between LTE and digital broadcasting, some studies have been carried out to analyze compatibility between these two systems through ergodic capacity [12], measurements testbed [13][14], and both simulation and measurements [15].…”
Section: Introductionmentioning
confidence: 99%